Digital Literacy-Based Entrepreneurial Education Strategies For Individuals With Disabilities in Mojokerto To Support SDGS on Social and Economic Inclusion - Setyowati, Eko Mety; Wahyudi, Dwi; Sudarmiatin; Firmansyah, Rizky (Economics and Business Journal (ECBIS), 2024)
Individuals with disabilities are often marginalized in accessing entrepreneurship education, limiting their economic opportunities. Digital literacy offers a solution to create entrepreneurial opportunities, aligning with technological advancements that promote social and economic inclusion. This study explores the development of digital literacy-based entrepreneurship education strategies for individuals with disabilities in Mojokerto. The innovation of this research lies in its integration of digital literacy with entrepreneurship education, a relatively underexplored approach. The study addresses the urgent need to increase participation of individuals with disabilities in the digital economy, in line with SDGs 8 and 10. Using a qualitative approach, the study conducted in-depth interviews and observations with individuals with disabilities and instructors. Findings show that digital literacy enhances participants' ability to engage in digital markets, understand online marketing, and use technology for business management. Participants reported greater self-confidence and the ability to start their own businesses after completing the program. The study underscores the need for a technology-based entrepreneurship curriculum and digital literacy training, to provide more inclusive and empowering opportunities for individuals with disabilities, supporting SDGs on social and economic inclusion